Quantum phase transitions in transverse field spin models from statistical physics to quantum information - Dutta, Amit 1968- (Cambridge University Press, 2015)
"Discusses the fundamental connections between the physics of quantum phase transitions and the technological promise of quantum information, non-equilibrium quantum dynamics and adiabatic quantum computations"..
Includes bibliographical references and index
Keywords: Phase transformations (Statistical physics); Phase rule and equilibrium; Quanteninformatik; Quantenphasenübergang; Spinmodell